2005
DOI: 10.1002/art.21440
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three comorbidity measures for predicting health service use in patients with osteoarthritis

Abstract: Objective. To compare the ability of 3 database-derived comorbidity scores, the Charlson Score, Elixhauser method, and RxRisk-V, in predicting health service use among individuals with osteoarthritis (OA). Methods. The study population comprised 306 patients who were under care for OA in the Veterans Affairs (VA) health care system. Comorbidity scores were calculated using 1 year of data from VA inpatient and outpatient databases (Charlson Score, Elixhauser method), as well as pharmacy data (RxRisk-V). Model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 42 publications
5
63
2
1
Order By: Relevance
“…Based on an extensive review, Sharabiana et al [23] found that if a comorbidity measure were necessary, the Elixhauser comorbidity score might be the best choice, but they had reservations that the results might differ based on the patient group and the outcome being investigated. However, one must consider that predictive performance of all the comorbidity index scores was not only outcome; the risk-adjustment method also had bearing [17], as was seen in patients with osteoporosis [6,15]. Based on our results, we conclude that if consideration of patient comorbidities is necessary to achieve a particular purpose, then the Elixhauser comorbidity score would seem the best for predicting patient HRQoL, pain, and satisfaction 1 year after THA.…”
Section: Discussionmentioning
confidence: 70%
“…Based on an extensive review, Sharabiana et al [23] found that if a comorbidity measure were necessary, the Elixhauser comorbidity score might be the best choice, but they had reservations that the results might differ based on the patient group and the outcome being investigated. However, one must consider that predictive performance of all the comorbidity index scores was not only outcome; the risk-adjustment method also had bearing [17], as was seen in patients with osteoporosis [6,15]. Based on our results, we conclude that if consideration of patient comorbidities is necessary to achieve a particular purpose, then the Elixhauser comorbidity score would seem the best for predicting patient HRQoL, pain, and satisfaction 1 year after THA.…”
Section: Discussionmentioning
confidence: 70%
“…In contrast to a previous analysis from our institution [4], we examined BMI as a continuous variable and in eight categories, which avoided loss of information and loss of power. In addition, we identified and adjusted for comorbidities using the Elixhauser algorithm, which is more strongly associated with healthcare use and costs than the Charlson classification [8]. Two studies [14,21] relied on administrative data from the Nationwide Inpatient Sample to address the impact of obesity on some THA outcomes, including costs.…”
Section: Discussionmentioning
confidence: 99%
“…13 Of the 70 citations using Elixhauser in cancer research since 2005, only 1 compared Elixhauser with Charlson. 14 Weight loss and obesity are included in the Elixhauser but not the Charlson measure.…”
mentioning
confidence: 99%